Mixed RF-VLC Relaying Systems for High-Speed Rail Communication - Rupender Singh; Ijaz Ahmad; Jyrki Huusko (IEEE Photonics Journal, 2023)
In the proposed system setup, a communication link is established between base station (BS) and end-user (UE) via a relay node mounted on the high-speed train (HST). The information is conveyed over backhaul RF links between BS and relay and over VLC links between relay and UE inside the train. It is assumed that RF links are encountered with dual shadowing due to slow-moving vehicles and pedestrians. Moreover, the relay node is not able to estimate the channel information perfectly due to HST mobility. Firstly, the statistical characteristics, such as the probability density function (PDF) and cumulative distribution function of the BS-relay link, are derived under imperfect channel information. Then, the system performance is examined by deriving the two key metrics, outage probability, and average bit error rate. Furthermore, we investigate the secrecy performance of the proposed system when the RF eavesdropper overhears the link between BS and relay and the VLC eavesdropper captures the information via the relay-UE link. To this end, the secure outage probability is derived into a closed form. Our results reveal that the proposed system setup can be adopted as a network architecture for existing as well as for future HST networks.